Some Aspects of Anti-Corruption Practice Formation in Muscovy (the End of XVI-XVII Centuries) - Alexander Vasilyevich Agrashenkov; Alexandra Viktorovna Lagun; Anastasia Vitalyevna Procopchuk (Управленческое консультирование)
The article analyzes the specific conditions that influenced on the formation of the functioning features of judicial and administrative authorities of the Moscow State (the end of XVI - XVII centuries). The causes of tolerant public attitude towards corruption are discovered. The process of the state anti-corruption practice formation is examined.